“We buy what we wanna be”: Understanding the effect of brand identity driven by consumer perceived value in the luxury sector - Xi, Xi; Yang, Jing; Jiao, Kaiwen; Wang, Shanshan; Lu, Tianxiang (Frontiers in Psychology, 2022)
Prior studies focused on consumer satisfaction and loyalty have brought undeniable benefits to luxury brand marketing but are not sufficient to ensure a long-lasting and profitable customer-brand relationship in the new setting. Brand identity provides a valuable exploration of this issue. However, the current measurement of brand identity is relatively simple, and there is no clear answer to what factors encourage brand identity development. This study attempts to address this gap by dividing the brand identity structure from a multi-dimensional perspective, considering the role of luxury consumer perceived value and brand information quality in shaping the brand identity. Data was gathered by an online questionnaire survey from Chinese consumers who had purchased luxury jewelry, employing regression methods for analysis. The results show that four predictors representing luxury consumer perceived value all have a significant impact on the brand’s social identity and personal identity. In addition, brand information quality also positively moderates the relationship between the luxury consumer perceived value and the brand’s social identity. This study opens new horizons for considering dimensions other than the satisfaction or intention to use, expanding the applications of brand identity in a new context. The results contribute to increasing the awareness level of brand identity for luxury brand practitioners and offering them a new method of market strategy.